Noninvasive prenatal testing in routine clinical practice for a high-risk population: Experience from a center. Issue 41 (October 2016) - Qi, Guijie; Yi, Jianping; Han, Baosheng; Liu, Heng; Guo, Wanru; Shi, Chong; Yin, Lirong
Abstract : Abstract: This study aimed to summarize the effects of noninvasive prenatal testing (NIPT) on aneuploidy among high-risk participants in Tangshan Maternal and Children Health Hospital. NIPT or invasive prenatal diagnosis was recommended to patients with a high risk of fetal aneuploidy from February 2013 to February 2014. Patients who exhibited eligibility and applied for NIPT from January 2012 to January 2013 were included in a comparison group. The rates of patients who underwent invasive testing, declined to undergo further testing, and manifested trisomies 21, 18, and 13 were compared between two groups. Follow-up data were obtained from the participants who underwent NIPT from 2013 to 2014. A total of 7223 patients (3018 and 4205 individuals before and after NIPT) were eligible for analysis. After NIPT was introduced in 2013 to 2014, 727 patients (17.3%) underwent invasive testing, 2828 preferred NIPT (67.3%), and 650 declined to undergo further testing (15.5%). A total of 34 cases of trisomies 21, 18, and 13 (0.8%) were found. In 2012 to 2013, 565 patients (18.7%) underwent invasive testing and 2453 declined to undergo further testing (81.3%). A total of 7 cases of trisomies 21, 18, and 13 were documented (0.2%). Of these cases, 24 were found from NIPT and 10 cases were found from invasive testing. The number of participants who declined to undergo further testing significantly decreased after NIPT was introduced (81.3% vs. 15.5%, P < 0.001). The sensitivity and specificity of NIPT for trisomies 21, 18, and 13 were 100% and 99.9%, respectively. The detection rates of NIPT for trisomies 21, 18, and 13 also significantly increased (0.2% vs. 0.8%, P < 0.001). By contrast, the overall rates of invasive testing remained unchanged (18.7% vs. 17.3%, P = 0.12). The positive predictive values of NIPT for trisomies 21, 18, and 13 were 100%, 83.3%, and 50.0%, respectively. The false positive rates of NIPT were 0% and 0.04%. With NIPT implementation in clinical practice, the rate of declining a follow-up test among high-risk women was decreased and the detection rate of prenatal chromosomal aneuploidy for trisomies 21, 18, and 13 was increased without requiring numerous invasive procedures.